Investigation of Soil Arching with Centrifuge Tests - Iglesia, Geraldo R; Einstein, Herbert H; Whitman, Robert V (Journal of geotechnical and geoenvironmental engineering, 2014)
AbstractThe classic experiment of a yielding trapdoor in (two-dimensional) plane strain beneath a granular mass is revisited, this time in the high-gravity environment of a geotechnical centrifuge. High-speed acquisition of load and displacement data makes it possible to examine the arching behavior of geomaterials. Results indicate the formation above the trapdoor of a physical arch, which evolves from an initially curved configuration to a triangular shape and ultimately to a prismatic sliding mass with vertical sides. Simple expressions for the reduced load caused by arching are proposed. Predictions using these expressions compare favorably with test measurements, paving the way for potential application to the design of underground structures.